(untitled) (REMUNOM, 2024)
This article aims to analyze Law 6.015/73, known as the Public Records Law, but specifically the deadlines for death registration. In short, death registration, in particular, is essential for the legal validation of acts carried out after the death of an individual, since untimely registration can lead to several legal and administrative complications. The controversy lies in the way in which the rigidity of legal deadlines affects the families of the deceased, prolonging suffering and worsening their economic condition. Therefore, the objective of this research is to analyze the provisions of Law 6.015/73 relating to late death registration, with the purpose of understanding their impacts and proposing regulatory reforms that make legal deadlines more flexible, as well as ensuring that death registration is carried out in an accessible manner, ensuring rights such as death pension and other benefits. Based on these analyses, the methodology used will be theoretical, through bibliographical research that will involve the analysis of legislation, doctrines and academic dissertations related to the topic.